Risk factors and prognosis of seizures in adults with community-acquired bacterial meningitis in Denmark: observational cohort studies - Larsen, Fredrikke Tove Birgitta Dam (BMJ Open, 2019)
OBJECTIVE: To examine predefined risk factors and outcome of seizures in community-acquired bacterial meningitis (CABM). DESIGN: Observational cohort studies SETTING: Denmark PARTICIPANTS: In the derivation cohort, we retrospectively included all adults (>15 years of age) with CABM in North Denmark Region from 1998 to 2014 and at Hvidovre and Hillerød hospitals from 2003 to 2014. In the validation cohort, we prospectively included all adults (>18 years of age) with CABM treated at all departments of infectious diseases in Denmark from 2015 to 2017. PRIMARY AND SECONDARY OUTCOME MEASURES: In the derivation cohort, we used modified Poisson regression to compute adjusted relative risks (RRs) with 95% confidence intervals for predefined risk factors for seizures during CABM as well as for risks of death and unfavourable outcome assessed by the Glasgow Outcome Scale score (1-4). Next, results were validated in the validation cohort. RESULTS: In the derivation cohort (n=358), risk factors for seizures at any time were pneumococcal aetiology (RR 1.69, 1.01–2.83) and abnormal cranial imaging (RR 2.27, 1.46–3.53), while the impact of age >65 years and immunocompromise was more uncertain. Examining seizures occurring after admission, risk factors were abnormal cranial imaging (RR 2.23, 1.40–3.54) and immunocompromise (RR 1.59, 1.01–2.50). Seizures at any time were associated with increased risks of in-hospital mortality (RR 1.45, 1.01–2.09) and unfavourable outcome at discharge (RR 1.27, 1.02–1.60). In the validation cohort (n=379), pneumococcal aetiology (RR 1.69, 1.10–2.59) and abnormal cranial imaging (RR 1.68, 1.09–2.59) were confirmed as risk factors for seizures at any time. For seizures occurring after admission, only pneumococcal meningitis (RR 1.92, 1.12–3.29) remained significant. Seizures at any time were also associated with in-hospital mortality (RR 3.26, 1.83–5.80) and unfavourable outcome (RR 1.23, 1.00–1.52) in this cohort. CONCLUSIONS: Pneumococcal aetiology, immunocompromise and abnormal cranial imaging were risk factors for seizures in CABM. Seizures were strongly associated with mortality and unfavourable outcome.